Stability of Cayley dynamic systems with impulsive effects - Awais Younus; Gulnaz Atta; Ahmad Aloqaily; Nabil Mlaiki; Thabet Abdeljawad (Journal of Inequalities and Applications, 2023)
Abstract Linear dynamic systems with impulsive effects are considered. For such a system we define a new impulsive exponential matrix. Necessary and sufficient conditions for exponential stability and boundedness have been established. The fundamental tool is an impulsive exponential matrix for exponential stability.